Estratégia de recuperação de área de manguezal através de indução ao crescimento e viveiros IN SITU. - Urtiga, Sebastião Pereira (2024)
Mangrove ecosystems are of great importance due to their rich biodiversity and vital role in protecting coastal zones and sustaining riverside communities. In Brazil, these ecosystems stretch along 6,800 km of coastline, covering nine states in the Northeast. They are inhabited by species such as Rhizophora mangle (Red Mangrove), Laguncularia racemosa (White Mangrove), and Avicennia schaueriana (Black Mangrove or Canoé), which have unique adaptations to survive in flooded environments subject to tides. Indiscriminate deforestation of mangroves has led to the degradation of these ecosystems, prompting efforts for their recovery. This work proposes the restoration of degraded areas in Bayeux, Paraíba, through the planting of seedlings of the mentioned species, as well as the development of an in situ seedling production method involving the participation of the riverside community. The objectives of the study include evaluating mangrove recovery strategies using low-cost, in situ germination box systems. Specific objectives are to demonstrate the floating germination box system, compare its effectiveness with fixed-ground germination boxes for different mangrove species, and determine growth models for seedling production planning. Preliminary results show that the tested germination box models yield promising results, especially the floating ones, suitable for seedling production in small areas. However, fixed-ground models demonstrated higher germination and growth rates. The Gompertz Growth Model proved useful for production planning and resource allocation in this context. These recovery efforts are essential to protect and preserve mangroves, ensuring their long-term ecological and socio-economic significance.